Herbert Bayard Swope correspondence - Swope, Herbert Bayard, 1882-1958.
Chiefly correspondence between Swope and Felix Frankfurter discussing foreign affairs, politics, and various prominent individuals of the era. Subjects include economic policies of the Roosevelt administration; relations with the Soviet Union; the rise of the Nationalsozialistische Deutsche Arbeiter-Partei, the Nazi Party in Germany; and the importance of the 1936 Olympic Games to Germany. Individuals mentioned include Bernard M. Baruch, Benjamin V. Cohen, Thomas G. Corcoran, Adolf Hitler, Joseph P. Kennedy, John Maynard Keynes, and Franklin D. Roosevelt. Includes copies of several letters from Frankfurter to Joseph P. Kennedy.
Journalist and policy consultant.
Collection material in English.
Keywords: Baruch, Bernard M. -- 1870-1965.; Cohen, Benjamin V; Corcoran, Thomas G; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Hitler, Adolf, -- 1889-1945.; Kennedy, Joseph P. -- 1888-1969.; Kennedy, Joseph P. -- 1888-1969 -- Correspondence; Keynes, John Maynard, -- 1883-1946.; Roosevelt, Franklin D. -- 1882-1945.; Nationalsozialistische Deutsche Arbeiter-Partei.; New Deal, 1933-1939.; Germany -- Politics and government -- 20th century; Soviet Union -- Foreign relations -- United States; United States -- Economic policy -- 1933-1945.; United States -- Foreign relations -- 1933-1945.; United States -- Foreign relations -- Soviet Union; United States -- Politics and government -- 1933-1945.; Consultants; Journalists